Knowledge sharing model for Fakulti Sains Komputer & Sistem Maklumat Institutional Repository - Hussain, Bibi Zuraidah (2010)
Scholarly communication activities such as journal publication and technical writings have been enhanced with the utilization of internet technology. Institutional Repository (IR), which is formed on the Internet, is expected to serve the needs of academic institutions for storing their scholarly publications and research materials. However, storing the publication in IR alone does not guarantee other academicians to share its value. In order to get benefit from other people publications as well as to share it with others, IR should be made more interactive or in other words, there are features of sharing knowledge in IR to get their interest. This research will contribute in bringing together research in IR and Knowledge Sharing. A study on both areas had been done and how these two concepts can collaborate in resulting better understanding of IR implementation. Knowledge Sharing features have been recognized to be added in IR namely content requirements, personalization and teamwork functions. Questionnaire surveys by Knowledge Management experts have helped in choosing the right features and functions. The proposed model and prototype based on the model has been developed.